Organizational Resilience: The Perspective of Strategic Human Resource Management In the Disruption Era - Suryaningtyas, Dianawati; Dwiatmadja, Christantius; Sedyastuti, Kristina (APMBA (Asia Pacific Management and Business Application), 2022)
The disruption era includes the fourth industrial revolution, climate change, and the Covid-19 pandemic. Education, the economy, business, and tourism, among other areas, are all affected by the disturbance. The purpose of this research is to examine how organizational resilience is implemented in a hotel from the perspective of strategic human resource management. The study employs a qualitative approach, with data collected through in-depth interviews and data processed through narrative. According to the conclusions of this study, the strategic roles of human resource executives or leaders are critical in dealing with organizational crises. This study contributes to knowledge by constructing propositions to establish a mini-theory.